Modeling the Proterozoic basement’s effective stress field, assessing fault reactivation potential related to increased fluid pressures in south central Kansas and north central Oklahoma, and improving seismic imaging of basement faulting within Wellington and Anson-Bates Fields, Sumner County, Kansas - Keast, Ryan Taylor (Kansas State University, 2018)
South-central Kansas has experienced an increase in seismic activity within the Proterozoic basement over the past 10 years. In 2009, Oklahoma seismic stations recorded 50 earthquakes statewide, a 200% increase from 2008. Oklahoma Geological Survey (OGS) seismograph stations recorded 1,028 in 2010, an increase of over 2000% from 2009. Between 2000-2012, Kansas experienced only 12 earthquakes statewide. Beginning in September 2013, clusters of seismic events in south-central Kansas began to increase. In 2015 alone, Kansas seismograph stations recorded 448 earthquakes, of which 166 resulted in a magnitude 2.0 or greater. Since 2013, United States Geological Survey (USGS) seismograph stations have recorded over 12,000 earthquakes within Kansas and Oklahoma. Pore fluid pressure increases associated with recent high-rate wastewater injection into the dolomitic Arbuckle disposal zone are hypothesized as cause of reactivation of the faulted study region’s Proterozoic basement. Although the magnitude of fluid-pressure change required for reactivation of these faults is likely low given failure equilibrium conditions in the midcontinent, heterogeneities (i.e. permeability, porosity, fluid pressure) in the basement could allow for a range of fluid pressure changes associated with injection. This research aims to quantify the fluid pressure changes responsible for fault reactivation of the Proterozoic basement. To address this issue, we use 97 earthquake focal mechanisms and over 12,000 seismic events, from the USGS catalog, within an area encompassing ~ 4,000 km². Focal mechanism data was utilized to determine the regional stress field present within the study region. Nodal plane data extracted from the focal mechanisms was crucial to identifying lineaments within the underlying basement complex. A 3D seismic dataset covering the Wellington and Anson Bates Fields in north central Sumner County, Kansas was utilized for enhanced structural delineation of an interpreted faultnetwork affecting the Mississippian and Arbuckle Groups, to investigate whether it impacts the underlying granitic basement and its complex network of potentially interconnected fault planes. Smoothed similarity and spectral whitening analyses were applied to the dataset to improve depth of investigation and uncover fault lineaments masked by seismic attenuation due to increasing depth. An interpreted network of fault planes at depths of 3.5 km was uncovered beneath Wellington Field. The lineaments are well aligned with known structural features present within the Proterozoic basement, the Central Kansas Uplift and the Nemaha Ridge-Humboldt fault zone.
Keywords: Fault reactivation; Induced seismicity; Improving seismic imaging; Proterozoic basement; Wastewater injection; Effective stress